An atomic redistribution study of the phase transformation kinetics of maraging-300 steel - Silva, Jean Jefferson Moraes da (2018)
Maraging steels are a class of Fe-based alloying steels that are age-hardened by the precipitation of finely dispersed intermetallic compounds in a low-carbon martensitic matrix. The combination of appropriate mechanical and magnetic properties makes it a suitable material for strategic applications in the aeronautical, aerospace and nuclear industries. The main alloying elements in this steel are Ni, Co, Mo and Ti. Carbon is considered an impurity, and the high nickel content (18 wt% Ni) ensures that martensite (α′) forms on air cooling. Thermal processing of maraging steels involves a solution treatment, usually at 820°C for 1 h, to homogeneously dissolve the alloying elements at the austenitic matrix at this temperature. The formed low carbon bcc martensitic matrix is then hardened by fine-scale precipitation of intermetallic compounds at temperatures of 400–650°C (ageing process), induced by the redistribution of atoms. Precipitates like the Ni3(Ti,Mo) η-phase, Fe2Mo Laves phase, S phase, ω phase, and Fe7Mo6 μ-phase were reported and reversion to austenite (γ) was also noticed at higher temperatures and longer ageing times. In maraging steels, the known precipitates present nanometric scale with dimensions between 1 and 50 nm. Besides this, the low volume fraction of such phases makes them hard to analyse. Because of this, too many uncertainties still exist regarding the precipitation kinetics in this material and there are no time-temperature-transformation (TTT) curves for this grade of maraging steel on literature. Because of the high Fe content of Maraging-300 steel, transmission Mӧssbauer spectroscopy (TMS) was chosen as a technique capable of providing valuable information about atomic mobility in this material. In this thesis, Maraging-300 steel was subjected to thermal processing resulting in 25 different ageing conditions. Transmission Mӧssbauer spectroscopy (TMS) – with the aid of transmission electron microscopy (TEM), X-ray diffraction (XRD), optical microscopy, and Vickers hardness measurements – has been used to investigate the effect of the mobility and configuration of the non-iron atoms on the phase transformation and precipitation behaviour of the steel. Ageing temperatures from 440 to 600°C for times from 1 to 100 h of ageing were studied. The key findings of this work revealed that the precipitation of intermetallic compounds in a bcc Co-rich martensitic matrix occurs in most of the conditions studied. The atomic redistribution is intense in the first hours of ageing and Ni, Mo and Ti are the main elements that form precipitates. Metastable phases appear at low ageing temperatures and reverted austenite was evidenced at higher temperatures and longer ageing times. At higher ageing temperatures (≥ 520°C) the Fe content of the martensitic matrix decreases with ageing time, and as soon as austenite begins to form much of the atomic redistribution occurs mainly between this phase and the precipitates. Also at these latter conditions a crystalline/magnetic transition zone was detected in the material.